Caracterização do risco de hematomas em carcaças bovinas - Pellecchia, Arquimedes José Riobueno [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Bruises on beef cattle carcasses are common worldwide causing important economic losses throughout the beef chain. The aim of this study was to characterize bruises occurrences on cattle carcasses, describing the number, location and time of occurrence, considering the animal categories and the distance from the farms to the slaughterhouse as underlying factors. The study was carried out in a commercial slaughterhouse located at São Paulo state (Brazil), with a daily slaughter capacity of 800 animals, assessing 22,324 carcasses. The bruises were characterized according to the area of occurrence in the carcass (forequarter, loin, ribs and hindquarter) and color, classifying as new (those with bright red coloring) and old (those with brown or yellow coloring). The numbers of bruises per carcass (total, new and old) were analyzed using generalized linear models, applying the GLIMMIX procedure of SAS statistical software and assuming the Poisson distribution for all dependent variables. The post hoc Tukey test was performed for comparison of means. To assess the risk of bruising on carcasses, a model of logistic regression was used with the application of SAS GENMOD procedure, considering as dependent the following variables: occurrence of total number of bruises (TNB), recent bruises (RB), old bruises (OB), bruises on the forequarter (BF), bruises on the loin (BL), bruises on the ribs (BR), and bruises on the hindquarter (BR). The percentages of carcasses with bruises were high for all animal categories, ranging from 62.24% for no castrated males to 83.8%, for cows. The most frequent bruises were those located on the ribs (49.02% of carcasses) and on the hindquarter (36.15%), when compared with the bruises observed on the forequarter (23.82%) and loin (14 59%). The greatest risk of ...

Os hematomas em carcaças bovinas ocasionam importantes perdas econômicas nas cadeias da carne de vários países. O objetivo desta pesquisa foi caracterizar a ocorrência de hematomas em carcaças bovinas, descrevendo o número, localização na carcaça e o tempo desde sua ocorrência, considerando as possíveis variações em função das categorias dos animais e das distâncias percorridas das fazendas até a planta frigorífica. O estudo foi realizado em uma planta frigorífica localizada no estado de São Paulo, com abate médio diário de 800 animais por dia, sendo avaliadas 22.324 carcaças. Os hematomas foram caracterizados, pelo local de ocorrência (dianteiro, lombo, costelas e traseiro) e pela avaliação de sua cor como novos (os de coloração vermelho vivo) e velhos (os de coloração marrom ou amarelo). Os dados sobre o número de hematomas nas carcaças (totais, novos e velhos) foram analisados por meio de modelos lineares generalizados, utilizando o procedimento GLIMMIX do pacote estatístico SAS versão 9.2. Neste modelo foi assumida a distribuição de Poisson para todas as variáveis dependentes. O teste post hoc de Tukey foi usado para a comparação de médias. Para avaliar o risco de ocorrência de hematomas nas carcaças foi utilizado um modelo de regressão logística com aplicação do procedimento GENMOD do SAS, considerando as seguintes variáveis dependentes: ocorrências de hematomas totais (HTO), de hematomas novos (HN), de hematomas velhos (HV), de hematomas no dianteiro (HD), de hematomas no lombo (HL), de hematomas na costela (HC) e de hematomas no traseiro (HT). As porcentagens de carcaças com hematomas foram altas para todas as categorias dos animais avaliadas, variando de 62,24% (observada em machos não castrados) a 83,8% (observada em vacas). Os hematomas ocorreram ...
Keywords: Bovino; Bovino - Carcaças; Hematoma; Saude animal; Produção animal; Animais - Transporte; Transportation